0233 Pain, Fatigue, and Altered Reactivity to a Repeated Physiological Stressor in Insomnia Patients: An Explanatory-Driven Analysis. (27th May 2020) - Goldstein, M R; Devine, J K; Dang, R; Chatterton, B; Scott-Sutherland, J; Yang, H; Mullington, J M; Haack, M
Abstract: Introduction: Fatigue and pain are prominent features of functional impairment in insomnia. This study aimed to better understand behavioral and physiological mechanisms of these complex relationships. Methods: 22 participants with insomnia disorder (DSM-5 criteria, 18 female, age 18-49yrs) and 22 good-sleeper controls (19 female, age 18-47yrs) completed two-weeks sleep logs and actigraphy recordings prior to coming to the laboratory for overnight polysomnography and subsequent daytime testing that included questionnaires, three trials of cold pressor test (CPT), and pain testing with blood draws collected throughout. Insomnia diagnosis was determined by a board-certified sleep specialist, and exclusion criteria included psychiatric history within past 6 months, other sleep disorder, significant medical conditions, and any medications within past two weeks with significant effects on inflammation, autonomic function, or other psychotropic effects. For CPT, participants were instructed to immerse hand in ice cold water for at least one minute and rate pain intensity throughout the immersion and 3-minute recovery. Data were analyzed with linear mixed models. Results: Per inclusion criteria, PSQI scores were differed between groups (insomnia: 10.2±2.7, range 7–16; control: 1.9±1.3, range 0–5; p <.001). Insomnia consistently reported higher daily fatigue ratings compared to controls ( p <.001), as well as higher spontaneous pain globally and across several specific domains ( p's : .007-.03). In response to CPT, groups did not differ in their initial tolerance (i.e. immersion duration, p =.41) or intensity ratings during immersion ( p =.88), however insomnia showed blunted recovery in intensity ratings ( p <.01). Control participants then showed an ability to habituate to repeated CPT by increasing immersion duration, whereas insomnia slightly decreased in tolerance across trials (Group effect: p <.05). Conclusion: These data indicate that habituation to and acute recovery from pain is deteriorated in chronic insomnia, which may be a key contributor to maintained pathophysiology over time and mechanism to target with comprehensive treatment. Support: Merck Inc. MISP# 51971 (investigator-initiated), NIH/National Center for Research Resources UL1-RR02758 and M01-RR01032 to the Harvard Clinical and Translational Science Center.